(untitled) (Abril – NEPA / UFF, 2016)
Livro resenhado: ATHAYDE, Manaíra Aires (Org.). Literatura Explicativa: ensaios sobre Ruy Belo. Lisboa: Assírio & Alvim, 2015. — DOI: http://dx.doi.org/10.21881/abriluff.2016n16a352